2002
DOI: 10.1111/j.2042-3306.2002.tb05385.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects on exercise metabolism of varying dietary starch and sugar proportions

Abstract: SummaryStudies of the effect of varying dietary carbohydrate compositions on exercise metabolism of horses are scarce. In the present study, the starch and sugar porportions were altered in the diet to 4 Standardbred horses. In a crossover experiment, the horses were offered a hay and oat diet, where the oats were substituted for barley syrup (BS) at 4 levels (BS 0, 0.5, 1.0 and 1.5 kg). Each diet was consumed for 21 days and both an incremental treadmill exercise test (IE) and a 40 min submaximal exercise tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
3
2
0
1
Order By: Relevance
“…As found in earlier studies, insulin concentration was greater at rest (before transportation) in horses on the high-concentrate diet (FOATS) compared with horses on the FONLY (Connysson et al, 2010; Jansson and Lindberg, 2012) and heart rate increased during transport (Smith et al, 1996; Doherty et al, 1997; Schmidt et al, 2010). However, exercise heart rate and plasma glucose concentration were not affected by diet, as previously observed (Pagan et al, 1987; Jansson et al, 2002; Jansson and Lindberg, 2012). The reason for this lack of dietary effect on plasma glucose is unclear but could be due to differences in the timing of feeding in relation to exercise (Duren et al, 1999; Pagan and Harris, 1999).…”
Section: Discussionsupporting
confidence: 85%
“…As found in earlier studies, insulin concentration was greater at rest (before transportation) in horses on the high-concentrate diet (FOATS) compared with horses on the FONLY (Connysson et al, 2010; Jansson and Lindberg, 2012) and heart rate increased during transport (Smith et al, 1996; Doherty et al, 1997; Schmidt et al, 2010). However, exercise heart rate and plasma glucose concentration were not affected by diet, as previously observed (Pagan et al, 1987; Jansson et al, 2002; Jansson and Lindberg, 2012). The reason for this lack of dietary effect on plasma glucose is unclear but could be due to differences in the timing of feeding in relation to exercise (Duren et al, 1999; Pagan and Harris, 1999).…”
Section: Discussionsupporting
confidence: 85%
“…The diet may also have supported a high glycogen content, as earlier observations on adult horses show that a high CP in forage, as in the present study, elevates glycogen content (Essen-Gustavsson et al, 2010). This study indicates that glycogen levels of young horses in training fed a high-energy forage-only diet are almost similar to what has been reported in adult Standardbred horses in training on both concentrate (572 mmol/kg DW (Jansson et al, 2002)) and forage diets (552 to 630 mmol/kg DW (Essen-Gustavsson et al, 2010)). …”
Section: Discussionsupporting
confidence: 77%
“…Other studies have shown no change (Vatistas et al 1999) in serum cortisol after 9 weeks of conditioning. The higher cortisol in fit RER horses fed a high NSC diet suggest that fit RER horses are probably more easily stressed on a high NSC diet, which is consistent with the excitable behaviour noted in Thoroughbreds fed high grain diets (Davidson et al 1998;Jansson et al 2002;Lindberg et al 2006), particularly those predisposed to RER (MacLeay et al 1999a;McGowan et al 2002).…”
Section: Discussionsupporting
confidence: 54%
“…The higher cortisol in fit RER horses fed a high NSC diet suggest that fit RER horses are probably more easily stressed on a high NSC diet, which is consistent with the excitable behaviour noted in Thoroughbreds fed high grain diets (Davidson et al . 1998; Jansson et al . 2002; Lindberg et al .…”
Section: Discussionmentioning
confidence: 99%